Clinical Yield of Electromagnetic Source Imaging and Hemodynamic Responses in Epilepsy: Validation With Intracerebral Data. (14th June 2022) - Abdallah, Chifaou; Hedrich, Tanguy; Koupparis, Andreas; Afnan, Jawata; Hall, Jeffrey Alan; Gotman, Jean; Dubeau, Francois; von Ellenrieder, Nicolas; Frauscher, Birgit; Kobayashi, Eliane; Grova, Christophe
Abstract : Background and Objectives: Accurate delineation of the seizure-onset zone (SOZ) in focal drug-resistant epilepsy often requires stereo-EEG (SEEG) recordings. Our aims were to propose a truly objective and quantitative comparison between EEG/magnetoencephalography (MEG) source imaging (EMSI), EEG/fMRI responses for similar spikes with primary irritative zone (PIZ) and SOZ defined by SEEG and to evaluate the value of EMSI and EEG/fMRI to predict postsurgical outcome. Methods: We identified patients with drug-resistant epilepsy who underwent EEG/MEG, EEG/fMRI, and subsequent SEEG at the Epilepsy Service from the Montreal Neurological Institute and Hospital. We quantified multimodal concordance within the SEEG channel space as spatial overlap with PIZ/SOZ and distances to the spike-onset, spike maximum amplitude and seizure core intracerebral channels by applying a new methodology consisting of converting EMSI results into SEEG electrical potentials (EMSIe–SEEG) and projecting the most significant fMRI response on the SEEG channels (fMRIp–SEEG). Spatial overlaps with PIZ/SOZ (AUCPIZ, AUCSOZ ) were assessed by using the area under the receiver operating characteristic curve (AUC). Here, AUC represents the probability that a randomly picked active contact exhibited higher amplitude when located inside the spatial reference than outside. Results: Seventeen patients were included. Mean spatial overlaps with the PIZ and SOZ were 0.71 and 0.65 for EMSIe–SEEG and 0.57 and 0.62 for fMRIp–SEEG. Good EMSIe–SEEG spatial overlap with the PIZ was associated with smaller distance from the maximum EMSIe–SEEG contact to the spike maximum amplitude channel (median distance 14 mm). Conversely, good fMRIp–SEEG spatial overlap with the SOZ was associated with smaller distances from the maximum fMRIp–SEEG contact to the spike-onset and seizure core channels (median distances 10 and 5 mm, respectively). Surgical outcomes were correctly predicted by EEG/MEG in 12 of 15 (80%) patients and EEG/fMRI in 6 of 11(54%) patients. Discussion: With the use of a unique quantitative approach estimating EMSI and fMRI results in the reference SEEG channel space, EEG/MEG and EEG/fMRI accurately localized the SOZ and the PIZ. Precisely, EEG/MEG more accurately localized the PIZ, whereas EEG/fMRI was more sensitive to the SOZ. Both neuroimaging techniques provide complementary localization that can help guide SEEG implantation and select good candidates for surgery.